Hope for the environment: Free enterprise and other economic regimes - William Jack Baumol (Fondazione Eni Enrico Mattei (FEEM), 1998)
This paper is the keynote speech delivered by Professor William Baumol at the First World Congress of Environmental Economists that was held in Venice on June 25-27, 1998. It analyses the situation of the environment under different economic regimes: the feudal society, Marxism and capitalism. After a brief description of the environmental situation in medieval England, in the Soviet Nations, in Eastern Europe, in China and in capitalist countries, the author concludes that each economic regime is worse than the other in terms of its environmental performance. There is, however, a message of hope in the long run for the environment. This hope lies in the abundance and growth, such as the world has never known, produced by the market economy. As abundance increases, as people cease being hungry, cease going around naked, cease having no houses, they begin to think about the environment. This has allowed concern about the environment to become a powerful political issue. Environmentalists will have to take advantage of this opportunity remembering, however, that the battle has just begun.
Keywords: B1; B2; 330; Hope; Environment; Economic regimes; Umweltschutz; Wirtschaftsordnung; Theorie